The spread of the African Independent Churches in postcolonial Southern Africa is a challenge to political and religious authorities : a case of the Lumpa Church in Zambia - Kondolo, Kapembwa (Department of Religious Studies, 2014)
Includes bibliographical references (leaves 70-80).